Studi Pendahuluan Keterampilan Pemecahan Masalah dan Metakognisi Siswa SMA berbasis UAPAC+SE - Nasir, Muhammad; Madlazim, Madlazim; Sanjaya, I Gusti Made (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2016)
Metacognition skills such as procedural knowledge, declarative knowledge, conditional knowledge, planning, monitoring, and evaluating are needed to understand problem-solving skills such as controlling and self-evaluation, planning and application, plan analysis, and understanding the problem. This study aims to describe problem-solving skills and student cognition in solving problems in physics subjects of XI IPA students in SMA Negeri 8 Samarinda. The population of the study sample amounted to 116 students grouped based on the results of physics achievement tests as many as 40 questions, divided into three groups, namely: groups of 32 students (28%), middle groups 61 students (53%), and groups under 23 students (20%). The research method used is a descriptive approach to the form of research in the form of case studies. Indicators of problem-solving skills, consisting of understanding the problem, analysis of the problem, planning, application of the plan, controlling & self-evaluation (UAPAC + SE). While metacognition uses the indicator of the Metacognitive Awareness Inventory (MAI). Based on data analysis, it can be concluded that the average problem-solving skills of upper group students (68%) are the high category, middle group students (34%), and lower group students (33%) are low categories. While the average metacognition skills are upper group students (66%) in the high category, middle group students (36%), and lower group students (33%) in the low category.